Commercial banana and macadamia plantations in a savanna matrix support high levels of arthropod diversity - Simba, Vhuawelo; Yekwayo, Inam; Mwabvu, Tarombera (African Entomology, 2023)
Expansion and intensification of agroecosystems is one of the major causes of habitat loss in the savanna biome in South Africa. As such, this study sought to determine the influence of commercial subtropical fruit plantations (banana and macadamia) on species richness, abundance, and composition of surface-active arthropods compared to the savanna biome. Given that pesticides and herbicides are applied from spring to early autumn in banana and macadamia plantations, we sampled in winter to reduce the potential impact of pesticides and herbicides. Surface-active arthropods were sampled using pitfall traps. Habitat type did not affect species richness and abundance of ants and spiders, as well as species richness of beetles. However, significantly greater abundance of beetles was recorded in the macadamia plantation compared to the banana and savanna. This could have been due to greater abundance of herbivorous beetles and other insects, which would have increased the diversity of predatory beetles. Furthermore, unlike the banana plantation, the macadamia plantation was characterised by a deep leaf litter layer and the presence of weeds and grasses, which probably increased abundance of beetles. Species composition indicated that the studied arthropod taxa associate with specific habitats, as demonstrated by the three habitats supporting different species composition. Despite savanna habitat not supporting high species richness or abundance of surface-active arthropods, we recorded the highest number of unique species of ants and spiders in the savanna rather than in the plantations. These results highlight the importance of natural landscapes in conservation of surface-active arthropods.